Multilevel Analysis on the Determinants of Overweight and Obesity among Primary School Students in Boyolali, Central Java (Journal of Maternal and Child Health, 2019)
Background: Fat and obesity are serious problems in children because they will continue into adulthood. Diarrhea occurs in groups of children under five years old (toddlers). According to the 2013 risk assessment, in Boyolali District the prevalence of obesity in children was 11.6% consisted of 7.5% fat and 4.1% obese. This study aimed to examine the determinants of overweight and obesity among primary school students in Boyolali, Central Java.Subjects and Method: This was an analytic observational study with a case-control design. The study was conducted at 25 elementary schools in Ngemplak sub-district, Boyolali, Central Java, from April 2017 to June 2018. A sample of 200 students was selected by fixed disease sampling. The dependent variable was fat and obese nutritional status. Independent variables were family income, pocket money, paternal BMI, maternal BMI, nutritional intake, and physical activity. The data were collected by questionnaire and analyzed by a multilevel linear regression.Results: Family income (b= 1.65; 95% CI= 8.28 to 2.48; p